2021
DOI: 10.32672/jse.v6i3.3246
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi dan Kuantifikasi Limbah Bahan Berbahaya Dan Beracun (LB3) Pada Industri X Di Kota Bandung

Abstract: The rapid development and development of the electronics industry in Bandung has both positive and negative impacts. The negative impact given is in the form of hazardous and toxic waste (HTW) which will have negative consequences if not managed properly. Evaluation of the management of HTW is an important thing to do to ensure that the management is in accordance with regulations. The purpose of this study is to identify and quantify the types and amounts of HTW in  industry X Bandung City. This company is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…Pemanasan global tidak hanya sangat ditakuti di Indonesia, tetapi juga salah satu peristiwa penting yang menjadi pembicaraan semua golongan internasional (Riani, 2012). Berbagai aktivitas yang dilakuan oleh manusia, terutama pembakaran bahan bakar fosil baik di kendaraan bermotor maupun industri, sehingga menyebabkan akumulasi gas rumah kaca (IPCC, 2001).…”
Section: Ekosistem Mangrove Merupakan Ekosistem Yangunclassified
“…Pemanasan global tidak hanya sangat ditakuti di Indonesia, tetapi juga salah satu peristiwa penting yang menjadi pembicaraan semua golongan internasional (Riani, 2012). Berbagai aktivitas yang dilakuan oleh manusia, terutama pembakaran bahan bakar fosil baik di kendaraan bermotor maupun industri, sehingga menyebabkan akumulasi gas rumah kaca (IPCC, 2001).…”
Section: Ekosistem Mangrove Merupakan Ekosistem Yangunclassified
“…Penelitian mengenai pengelolaan LB3 telah banyak dilakuakan seperti di rumah sakit Kota Batam [4], Rumah Sakit Gigi dan Mulut Universitas Padjadjaran Kota Bandung [5], RSUD dr Drajat Prawiranegara Kabupaten Serang [6], di industi tekstil [7] [8]. Pengelolaan LB3 di industri kertas [9] dan Perusahaan Listrik Negara PUSHARLIS UP2 WIII Bandung [10].…”
Section: Pendahuluanunclassified
“…Various research related to the textile industry in Bandung Regency has been carried out domestically, especially regarding the evaluation of the social, economic, and environmental impacts of the industry's existence (Aziz et al, 2020;Cahyani et al, 2020;Fitriani et al, 2018;Ginanjar et al, 2015;Harahap, 2019;Heriyadi et al, 2021;Muzri et al, 2022;Novianti & Sumeru, 2020;Oláh et al, 2020;Wardhani & Triatmaja, 2021), waste management efforts (Aisyah, 2022;Arifatunnisa et al, 2022;Hidayat & Sutrisna, 2018;Komarawidjaja, 2016;Rahmani, 2018)), land conversion (Aprilana & Darmawan, 2021;Nuraeni et al, 2017;Trisnasari et al, 2014), efforts to improve the quality and quantity of industrial products (Aulia & Suheri, 2017;Fathurohman et al, 2014), industrial business development efforts (Lucky & Rosmadi, 2017;Tachyan, Zaenudin;Rosmadi, 2018), and licensing institutional model (Efendi, 2014). However, no research has been found related to the implementation of regional spatial utilization policies in terms of the main program indications of spatial utilization directions in the textile and textile products industry in Bandung Regency.…”
Section: Introductionmentioning
confidence: 99%